As shown above, in one of the two pink semicircles whose diameter is the length of the side of a unit square, two violet semicircles, one green circle and one blue circle are symmetrically positioned. The red ellipse whose semi-minor axis is the radius of the cyan circle and whose major axis is parallel to one of the square sides is also positioned symmetrically, but tangent to both pink semicircles each at one point.
If the semi-major axis can be expressed as
where
Input the product as your answer.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By Pythagorean theorem on △ E G F , F G 2 = E G 2 + E F 2 ⇒ ( r g + r v ) 2 = r g 2 + ( r p − r v ) 2 ⇒ ( 4 1 + r v ) 2 = 1 6 1 + ( 2 1 − r v ) 2 ⇒ r v = 6 1 Using Descart’s circle theorem we calculate the radius of the blue circle: k b ⇒ r b = 1 2 1 = k v + k g + k p − 2 k v k g + k g k p + k p k v = 6 + 4 − 2 − 2 6 × 4 + 4 × ( − 2 ) + ( − 2 ) × 6 = 1 2
( x + 2 1 ) 2 + ( y − 1 2 5 ) 2 = 4 1 The semi-minor axis of the ellipse is b = r b = 1 2 1 .
If a is the major semi-axis of the ellipse, then its equation is a 2 x 2 + 1 4 4 y 2 = 1 Let l be the common tangent of the left pink semicircle C p and the ellipse and N ( x N , y N ) their point of tangency. Then, the equation of l as a tangent to the ellipse at N is a 2 x N x + 1 4 4 y N y = 1 The slope of l is m l = − 1 4 4 a 2 y N x N and the slope of line E N is m E N = x N − x E y N − y E = x N + 2 1 y N − 1 2 5 = 1 2 x N + 6 1 2 y N − 5 So, we have E N ⊥ l ⇒ m E N m l = − 1 ⇒ 1 2 x N + 6 1 2 y N − 5 ⋅ ( − 1 4 4 a 2 y N x N ) = − 1 ⇔ 1 4 4 a 2 y N ( 1 2 x N + 6 ) = x N ( 1 2 y N − 5 ) N belongs to both C p and the ellipse, thus we get the system ⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ ( x N + 2 1 ) 2 + ( y N − 1 2 5 ) 2 = 4 1 a 2 x N 2 + 1 4 4 y N 2 = 1 1 4 4 a 2 y N ( 1 2 x N + 6 ) = x N ( 1 2 y N − 5 ) Solving this system for the positive number a we get a = 8 1 1 5 1 ( 2 9 9 − 4 1 4 1 ) For the answer, a b c d e f g = 1 × 8 × 1 × 1 5 × 2 9 9 × 4 1 × 4 1 = 6 0 3 1 4 2 8 0 .